Os idosos e o sistema público de saúde no município de Santos, São Paulo - Silva, Marlene Valdice da (2006)
This task proposes to investigate the atendance of elderly people at the Health Public Service in Santos, SP. Its general goal is to investigate the relationship between the health needs from lhe elderly and the reality of public services. The methodology used has adopted procedures consolidated either in quantitative approach or in qualitative approach. Besides the data colecting, observation in loco and the writing of a field dictionary were dane. It algo looked for information about the physical space, routines, offered services, sociability of services and the roles played by each component of this scenary. The research went on by the interest of revealing the day by day reality of this service showing the attendance of the needs from the eldery people. The research revealed through situations registered in the field dictionary thar the interviewed people felt well received by the staff from the hospital. However, the services and the spaces do not hold the quantity of people. So there is a need for reestruturation. The search from elderly people for specializes atendance was clearly showed in the investigation